Entretien avec M. Nacoulma [producteur] (De 2000 à 2020, Deux Décennies de Films de Fiction Burkinabè: Acteurs/Actrices, Orientations Thématiques et Profils Esthétiques, 2023)
This interview with Yacouba Nacoulma focuses on his experience as a producer and director of fiction film.
Keywords: Actors; Aesthetics; Experience; Cinema